Psychological characteristics of suicide attempters among undergraduate college students in China: a cross-sectional study - Bob Lew; Augustine Osman; Caryn Mei Hsien Chan; Won Sun Chen; Norhayati Ibrahim; Cun-Xian Jia; Ching Sin Siau (BMC, 2021)
Abstract Background There is a need to understand the psychological characteristics of suicide attempters to prevent future suicide attempts. This study aims to examine potential differences between individuals who have attempted suicide and those who have not done so, on several risk and protective measures. Method Participants were 11,806 undergraduate students from seven provinces in China, of which 237 reported a non-fatal suicide attempt. We used the random numbers generator function within the SPSS to randomly select a control subset of 1185 participants to be used as the comparison group based on a 1:5 case-control ratio. Scores on three commonly used risk measures (depression, hopelessness, and psychache) and three protective measures (social support, self-esteem, and purpose in life) for suicidality were adopted to compare the responses of the two groups. Results Suicide attempters had indicated higher Median scores for all three risk factor measurements. Suicide attempters also reported significantly lower Median scores for all three protective factor measurements compared to non-suicide attempters. The results suggest that the suicide attempters' group had higher risks of suicidality compared to the non-attempter group. Conclusions Suicide attempters continued to report higher scores of risk factors and lower scores of protective factors, indicating that they may continue to be at a higher likelihood of a suicide attempt. Key protective factors should be identified for each individual in order to deliver appropriate clinical interventions to reduce their risk of reattempting.